Penerapan Terapi Murottal Al-Qur’an Surah Ar-Rahman terhadap Kualitas Tidur Lansia di Dusun Ngendak - Anisa Melia Yahya; Anjar Nurrohmah (Lembaga Pengembangan Kinerja Dosen, 2023)
Background: Poor sleep quality is a disorder that often occurs in the elderly. The impact of sleep disturbances in the elderly can result in the body's inability to restore its original state, causing weakness, headaches, drowsiness, and fatigue. Treatment of sleep quality disorders is carried out with non-pharmacological treatment, one of the non-pharmacological therapies that can be done is Al-Qur'an Murottal Therapy. Purpose: To find out changes in the level of sleep quality in the elderly before and after carrying out murottal Al-Qur'an therapy. Method: This application uses a descriptive method on 2 respondents, done 1 time in 7 consecutive days. The instrument used is the Pittsburgh Sleep Quality Index (PSQI) to measure sleep quality. Results: Treatment of sleep quality disorders with Al-Qur'an murottal therapy which is given 1 time for 7 days in 15 minutes can affect the level of sleep quality of respondents, so that there is a change in the sleep quality score of the elderly. Conclusion: The application shows that after the Al-Qur'an murottal therapy there was an increase in the quality of sleep in both respondents from poor sleep quality to light sleep quality.